SWOT Analysis of Formation of Modern Irrigation Management Unit in DI Kromong (Kromong Irrigation Area), Kabupaten Mojokerto - Rochmad Afandi; Nadjadji Anwar; Theresia Sri Sidharti (Journal of Infrastructure & Facility Asset Management, 2021)
Kromong Irrigation Area (Kromong Irrigation Area), is an irrigation area that already has readiness for the implementation of irrigation modernization (Sari, 2019). Hence, it is necessary to establish a Modern Irrigation Management Unit (UPIM), as an initial step to start the modernization of irrigation in the irrigation area. To find out the readiness for the establishment of UPIM, the data are needed for the existing irrigation management. The data were collected by firstly, interviewing irrigation officials in charge of the Kromong Irrigation Area. Secondly, distributing questionnaires to determine SWOT indicators to irrigation officials and the Association of Water Users Farmers Association (GHIPPA) in the Kromong Irrigation Area. Furthermore, the results of the SWOT indicators are weighted and rated to determine the Internal Strategic Factor Analysis Summary (IFAS) and External Strategic Factor Analysis Summary (EFAS) of each irrigation management agency. The study found that the readiness of mandatory functions in UPIM at Dinas PU PSDA Provinsi Jawa Timur had the highest value in the TOWS strategy quadrant graph (2.41 , 3.17), followed by UPT Pengairan Pugeran (1.89 , 2.24), and UPT PSDA Brantas Korwil Surabaya (0.78 , 1.86). All agencies have more strengths and opportunities than their weaknesses and threats. Therefore, DI Kromong is ready to establish an UPIM.